2012
DOI: 10.1080/00750778.2012.758434
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of spaceborne radar to near-surface soil moisture in grasslands across southern Ireland

Abstract: Word Count: 7241Sensitivity of spaceborne radar to near-surface soil moisture in grasslands across southern IrelandThe amount of water stored in the soil is a key parameter for the energy and mass fluxes at the land surface and is of fundamental importance to many agricultural, meteorological, biological and biogeochemical processes. This study investigates the potential of retrieving surface soil moisture in grassland areas from a time series of 68 ENVISAT Advanced Synthetic Aperture Radar (ASAR) Wide Swath M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Cross-polarization is more sensitive to vegetation, as it captures vegetation response (backscattering) better than VV polarization. Barrett et al (2007), in a study to derive relative changes in soil moisture in the near-surface (0-5 cm) over an agricultural area in southern Ireland, observed that the growth of vegetation (grass) could cause attenuation of the radar signal (i.e., depolarisation effect due to volumetric scattering contribution). Pratola et al (2014) in a similar study, also carried out in southern Ireland, found that in winter, the distribution of soil moisture is rather homogenous over the SAR pixels, whereas a higher spatial variability was observed in summer.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Cross-polarization is more sensitive to vegetation, as it captures vegetation response (backscattering) better than VV polarization. Barrett et al (2007), in a study to derive relative changes in soil moisture in the near-surface (0-5 cm) over an agricultural area in southern Ireland, observed that the growth of vegetation (grass) could cause attenuation of the radar signal (i.e., depolarisation effect due to volumetric scattering contribution). Pratola et al (2014) in a similar study, also carried out in southern Ireland, found that in winter, the distribution of soil moisture is rather homogenous over the SAR pixels, whereas a higher spatial variability was observed in summer.…”
Section: Theoretical Backgroundmentioning
confidence: 99%